PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SD NEGERI 006 TRI MULYA JAYA KECAMATAN UKUI - Setyaningsih ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by low yields VI SD Negeri 006 Tri Mulya Jaya grade sciencestudents, 20 students only 10 students who completed their study results. The low yield is dueto learn science: (a) learning model used by teachers is conventional; (b) learning is teahinglearning, so that students become passive. The purpose of this research is to improve students'science learning outcomes through the implementation of cooperative learning model make amacth. This research is a class act who do as much as two cycles. The data used in this studyis the activity data and the teacher and student learning outcomes IPA. Based on the researchresults that the activity data and the results of teachers and students learn science hasincreased, this is evidenced by: (a) the activity of students has increased, at the first meeting Isikuls average student activity is 54.00%, at a meeting II I cycle average activity increased to62.00%, in the first meeting of the second cycle average of 75.00% of student activity and thesecond meeting of the second cycle increased by an average of 83.00% of student activity;and (b) the results of studying science increased in the initial data the percentage of studentswho completed is 50.00% with an average value of 61, the first cycle the percentage ofstudents who completed is 75.00% with an average value of 79, and the second cycle of thepercentage of students who completed is 85.00% with an average value of 76.5.